USULAN PERBAIKAN TATA LETAK FASILITAS PRODUKSI INDUSTRI KOPI STUDI KASUS CV. TRI ANOM AGROTEKTUR - Nabilla Saptaryana Martha; Irfan Ardiansah (Universitas Putera Batam, 2020)
Industrial layout is one of the important factors that affecting the efficiency of the production operation process, which can be seen from the material movement activities to be processed into products. CV. Tri Anom Agrotektur manages the coffee industry which is divided into 2 activity sectors, namely the upstream and downstream sectors. This study designed a proposal to improve the factory layout of the company’s upstream sector using qualitative methods and direct interviews with factory employees. In determining the layout improvement of the industry, it is necessary to first identify the production process, using the Process Flow Diagram and Process Flow Map. The data processing methods used are: Activity Relationship Chart (ARC), Activity Relationship Diagram (ARD), and Activity Allocation Diagram (AAD). Total area of the factory building is ± 1.072 m2, while the proposed total area of the building based on the area of the machine, the area of the employee’s movement and the additional area of production support room is ± 833 m2. The total proposed rooms are 23 rooms. Proposed improvements to the industrial layout can be use as company reference that is expected to increase productivity and reduce production costs